Integrating Immersive Learning and Interactive Media in Teaching Islamic Cultural History: A Qualitative Case Study - Novia Ramadhani; Wahyudin Nur Nasution (CV. Sakura Digital Nusantara, 2026)
Purpose – This exploratory qualitative case study describes the initial implementation of technology-based learning media (Wordwall, video, and PowerPoint) within Islamic Cultural History (ICH) learning at MTsN 2 Deli Serdang.Methods – The study involved five informants: one (ICH) teacher, a principal as a contextual informant, and three eighth-grade students. Data were collected naturally through eight classroom observation sessions, documentation studies, and five in-depth interviews. To comply with ethical standards for protecting minors, all student identities were anonymized, and visual documentation was digitally blurred.Findings – Based on observations and interviews, integrating interactive media reduced student passivity common in conventional lecture methods. Visual quizzes and videos helped direct student focus and facilitated historical recollection. However, given the small qualitative sample size, improvements in students' motivation, critical thinking, and social skills remained situational and did not reach full theoretical saturation. Practical implementation was also constrained by limited lesson time, infocus shortages, and the challenges of large crowd management due to noise during gamified quizzes. Research implications – This study offers context-specific qualitative insights into how interactive tools stimulate classroom engagement in madrasah settings. Originality – The findings reject macro-level generalizations or broad TPACK and self-determination claims, illustrating instead the practical challenges